2017
DOI: 10.1111/febs.13983
|View full text |Cite
|
Sign up to set email alerts
|

Emerin self‐assembly mechanism: role of the LEM domain

Abstract: At the nuclear envelope, the inner nuclear membrane protein emerin contributes to the interface between the nucleoskeleton and the chromatin. Emerin is an essential actor of the nuclear response to a mechanical signal. Genetic defects in emerin cause Emery-Dreifuss muscular dystrophy. It was proposed that emerin oligomerization regulates nucleoskeleton binding, and impaired oligomerization contributes to the loss of function of emerin disease-causing mutants. We here report the first structural characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…We tested binding between the tail region common to lamins A and C (LamIgF comprising aa 411 to aa 566) and these emerin fragments. As previously published, the whole emerin nucleoplasmic region from aa 1 to aa 221 is poorly soluble ( 34 ). We thus produced two overlapping emerin peptides, which we called EmN ( 26 ) and EmC (Figure 1A ).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…We tested binding between the tail region common to lamins A and C (LamIgF comprising aa 411 to aa 566) and these emerin fragments. As previously published, the whole emerin nucleoplasmic region from aa 1 to aa 221 is poorly soluble ( 34 ). We thus produced two overlapping emerin peptides, which we called EmN ( 26 ) and EmC (Figure 1A ).…”
Section: Resultsmentioning
confidence: 53%
“…We thus produced two overlapping emerin peptides, which we called EmN ( 26 ) and EmC (Figure 1A ). EmN (aa 1 to aa 187) comprises a LEM domain and a region that is intrinsically disordered ( 34 , 35 ). We previously showed that, in vitro , it can be observed either as a monomer or as an oligomer ( 26 ) (Figure 1B , left panel).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms by which emerin, an intrinsically disordered ‘transformer’ protein (Samson et al, 2016), senses force and signals in response to force are open questions. Emerin has at least two modes of self-association with the potential to form networks or filaments (Berk et al, 2014; Herrada et al, 2015; Samson et al, 2017). Other partners include nucleo/cytoskeletal proteins (e.g., F-actin, myosin 1c, tubulin), nuclear membrane proteins (e.g., LAP1, Samp1) and transcriptional regulators such as HDAC3, b-catenin and Lmo7 (Holaska et al, 2006; Berk et al, 2013b; Shin et al, 2013; Barton et al, 2015; Vijayaraghavan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It also interacts with lamin A/C, nesprin-1α and LUMA (Ellis, 2006 ; Liang et al, 2011 ). Emerin is able to self-assemble in vitro and it was suggested that the LEM domain configuration in the emerin multimers may modulate its interaction with chromatin and nucleoplasmic proteins (Berk et al, 2014 ; Samson et al, 2017 ). Depending on tissue, emerin was also described at alternative subcellular locations.…”
Section: Proteins Involved In Edmdmentioning
confidence: 99%